2016
DOI: 10.1039/c6nj01038e
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the synthesis of imidazo and triazolopyridines from dithioesters

Abstract: Various imidazo- and triazolo-pyridines were synthesised by the intramolecular cyclization of pyridine 2-methylamine and dithioesters under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…28 Ramesha et al described a simple and convenient procedure for obtaining imidazo[1,5-a]pyridines 52 from commercially available dithioesters 51 and 2-methylaminopyridines 50 using T 3 P in THF (Scheme 12). 29 Screening of various catalysts, solvents, and additives revealed that the optimal reaction conditions were 2-methylaminopyridine (1.1 equiv. ), T 3 P (1.0 equiv., 50% in EtOAc), and DMSO (2.0 equiv.)…”
Section: From 2-methylaminopyridines With Acidsmentioning
confidence: 99%
“…28 Ramesha et al described a simple and convenient procedure for obtaining imidazo[1,5-a]pyridines 52 from commercially available dithioesters 51 and 2-methylaminopyridines 50 using T 3 P in THF (Scheme 12). 29 Screening of various catalysts, solvents, and additives revealed that the optimal reaction conditions were 2-methylaminopyridine (1.1 equiv. ), T 3 P (1.0 equiv., 50% in EtOAc), and DMSO (2.0 equiv.)…”
Section: From 2-methylaminopyridines With Acidsmentioning
confidence: 99%
“…Even though, a range of methods are already reported for the generation of these valuable molecules but they have some limitations for instance involvement of toxic reagents, prolonged reaction times, limited substrate scopes, harsh reaction conditions, and tedious work-up procedures as well. [287][288][289] In order to overcome some of the above mentioned critical problems, Ravinder's group in 2016 reported an efficient and expedient way for the synthesis of a varied 3aryl [1,2,4]triazolo [4,3-α]pyridines 347 a-g from the oxidative cyclization of 2-(2-arylidenehydrazinyl)pyridines 346 utilizing RuCl 3 /oxone in 1,2-dichloroethane (DCE) as a solvent in a chemoselective manner (Scheme 114). [290] A detailed possible mechanism reported by the authors is stated in the Scheme 115.…”
Section: Oxidative Cyclization Of 2-(2-arylidenehydrazinyl)pyridines ...mentioning
confidence: 99%
“…Most synthetic approaches rely on various cyclocondensations of nucleophilic (2-aminomethyl)pyridine precursors, introducing a new five-membered ring. Typically, carboxylic acids [16][17][18][19][20], acyl anhydrides [21][22][23], acyl chlorides [24][25][26][27], esters [28], thioamides [29][30][31], dithionates [32,33], or thiocarbamates [34] are employed as electrophilic components, but oxidative cyclocondensations with aldehydes have also been showcased [35][36][37]. However, given the importance of these targets, new preparative methods are still in high demand.…”
Section: Introductionmentioning
confidence: 99%